2021
DOI: 10.3389/fcell.2021.777697
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Induced Osteonecrosis of the Femoral Head: Novel Insight Into the Roles of Bone Endothelial Cells in Pathogenesis and Treatment

Abstract: Steroid-induced osteonecrosis of the femoral head (SONFH) is a disease characterized by the collapse of the femoral head. SONFH occurs due to the overuse of glucocorticoids (GCs) in patients with immune-related diseases. Among various pathogenesis proposed, the mechanism related to impaired blood vessels is gradually becoming the most convincing hypothesis. Bone endothelial cells including bone microvascular endothelial cells (BMECs) and endothelial progenitor cells (EPCs) play a crucial role in the maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 114 publications
0
23
0
Order By: Relevance
“…In addition, oxidative stress is also involved in regulating the adipogenesis and osteogenesis of mesenchymal stem cells to influence the progression of ONFH ( 46 ). Endothelial progenitor cells play an essential role in maintaining the normal structure and function of bone vessels, and the impaired angiogenesis, thrombosis and fat embolism caused by abnormal apoptosis and dysfunction of bone endothelial cells are involved in the pathogenesis of ONFH ( 47 ). Therefore, these directions deserve more time and funds for more in-depth and comprehensive research in the future.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, oxidative stress is also involved in regulating the adipogenesis and osteogenesis of mesenchymal stem cells to influence the progression of ONFH ( 46 ). Endothelial progenitor cells play an essential role in maintaining the normal structure and function of bone vessels, and the impaired angiogenesis, thrombosis and fat embolism caused by abnormal apoptosis and dysfunction of bone endothelial cells are involved in the pathogenesis of ONFH ( 47 ). Therefore, these directions deserve more time and funds for more in-depth and comprehensive research in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Based on current trends, Mont et al [ 23 ] reported that the total number of individuals affected by ONFH is estimated to reach 20 million by next 10 years worldwide. Besides, the increase in annual publications is inseparable from the advances in basic research and clinical trials in recent years [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, uncontrolled neutrophil ROS production can lead to persistent vascular inflammation reactions contributing to some inflammatory diseases [ 31 ]. Moreover, the impaired blood vessels caused by dysregulation of bone endothelial cells are one of the most convincing mechanisms of SONFH [ 32 ]. Therefore, the vascular inflammation caused by high expression of CYBB may be related to SONFH.…”
Section: Discussionmentioning
confidence: 99%